1993
DOI: 10.1207/s15327752jpa6003_3
|View full text |Cite
|
Sign up to set email alerts
|

Rorschachs of Women Who Commit Homicide

Abstract: For a majority of the women who kill, the victim is a family member; the most frequent is a spouse, and the woman is very frequently a battered woman. Clinical reports on battered women suggest a set of psychological symptoms that develops out of spousal abuse (i.e., pervasive anxiety, hyperalertness, impaired memory and concentration, a narrowed focus on signs of danger, constricted affect, development of chronic psychophysiological illnesses, and pervasive feelings of hopelessness and helplessness). Psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
5
24
1
Order By: Relevance
“…On the other hand, it might also be possible that coping with the offence is actually more difficult for women than for men, which could explain the slightly increased external score for the female offenders compared to men. This explanation is in line with the results found in a study on women guilty of homicide [52]. The women in this study did not show capacity of internalising painful affects or a painful self-reflection, and they tended to externalise their affects.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it might also be possible that coping with the offence is actually more difficult for women than for men, which could explain the slightly increased external score for the female offenders compared to men. This explanation is in line with the results found in a study on women guilty of homicide [52]. The women in this study did not show capacity of internalising painful affects or a painful self-reflection, and they tended to externalise their affects.…”
Section: Discussionsupporting
confidence: 92%
“…Similar constricted cognitive structures have been observed in Rorschach protocols of Vietnam veterans [48]and in women who killed their battering spouse [49]. It can be speculated that the common denominator of the above deficiencies in coping is a rigid approach and a lack of plasticity in dealing with novel situations.…”
Section: Discussionsupporting
confidence: 63%
“…The results confirm some of the earlier findings on antisocial women (Gacono & Meloy, 1994) and women who, as a reaction to victimization, had committed homicide (Kaser-Boyd, 1993). The results reveal, as predicted, that a larger proportion of the offenders than the non-offenders displayed an inconsistent problem coping style.…”
Section: Discussionsupporting
confidence: 89%
“…However, Wood, Krishnamurthy, and Archer (2003) found that the Full scale and Verbal IQs correlated negatively with Form%, but did not correlate with the number of Rorschach responses (R) or Afr. Significant positive relationship between intelligence and R was found by Wagner, Young, and Wagner (1992) as well as Kaser-Boyd (1993). In this later study no association between intelligence and Lambda was found.…”
mentioning
confidence: 54%
See 1 more Smart Citation